Electrochemical modified electrodes based on metal-salen complexes - Fatibello-Filho, Orlando; Dockal, Edward Ralph; Marcolino-Junior, Luiz Humberto (Taylor & Francis Inc, 2007)
A general view of the electroanalytical applications of metal-salen complexes is discussed in this review. The family of Schiff bases derived from ethylenediamine and ortho-phenolic aldehydes (N,N'-ethylenebis(salicylideneiminato) - salen) and their complexes of various transition metals, such as Al, Ce, Co, Cu, Cr, Fe, Ga, Hg, Mn, Mo, Ni, and V have been used in many fields of chemical research for a wide range of applications such as catalysts for the oxygenation of organic molecules, epoxidation of alkenes, oxidation of hydrocarbons and many other catalyzed reactions; as electrocatalyst for novel sensors development; and mimicking the catalytic functions of enzymes. A brief history of the synthesis and reactivity of metal-salen complexes will be presented. The potentialities and possibilities of metal-Salen complexes modified electrodes in the development of electrochemical sensors as well as other types of sensors, their construction and methods of fabrication, and the potential application of these modified electrodes will be illustrated and discussed.
Keywords: metal-salen complexes; electrocatalysis; modified electrodes; PVC membranes